The Relationship Between Inventory Management Automation and the Performance of Supermarkets in Melaka - Nur Fatin Muhamad,; Hafizah Zulkipli, (Research in Management of Technology and Business, 2024)
In the present-day furiously competitive business landscape, organizations constantly strive for effectiveness, cost optimization, and economies of scale. To meet customer demands, many organizations rely on maintaining inventory. However, managing inventories effectively to achieve organizational goals has become a significant challenge for companies. Determining the optimal inventory levels and investment amounts to satisfy customer needs has proven to be a daunting task for numerous firms. Consequently, organizations have turned to current technology to deal with these problems. This study aims to assess the level of inventory management automation and the performance of supermarkets in Melaka. Furthermore, it seeks to identify the relationship between inventory management automation and supermarket performance in the region. Employing a quantitative research approach, a questionnaire serves as the primary data collection instrument. The study's respondents consist of supermarket employees in Melaka. A total of 190 employees have answered the questionnaire for this study. The collected data will be analyzed descriptively and through correlation using the Statistical Package for the Social Sciences (SPSS). The results of the study show that inventory management automation and performance have a high level of correlation. There is a significant relationship between Inventory Management Automation and Performance supermarkets in Melaka. Future researchers can benefit from the findings of this study.